COST BENEFIT ANALYSIS AND ITS ROLE IN INVESTMENT PROJECTS IN AGRICULTURE - Sorina Simona BUMBESCU; Alina VOICULESCU (Hyperion Economic Journal, 2014)
The investment projects have of particular importance for the development and progress of an organization. The development of investment projects involves making a decision and the existence of financial resources. The agriculture has specific features and contributes significantly to the gross domestic product, which is why channeling the investments to agriculture must be a priority. In this context, the cost-benefit analysis is a useful tool for evaluation and analysis of the investment projects, contributing significantly to the decision making regarding the choice of the optimal project. The objective of this article is to highlight the importance of cost-benefit analysis for the projects investment financed by the European Union through the Rural National Development Program 2007-2013, under axis IV LEADER. The article is structured in two parts which contains theoretical aspects and a case study. Thus it is made an overview of the investment, funding sources of the investment projects, the investment decision, the relevance of cost-benefit analysis for the investment projects. The case study aims to analyze the relationship between the results of the investment projects which include cost-benefit analysis and those that do not inlcude cost-benefit analysis.